Effect of Histatin-1 Proteins to Fibroblasts Growth Factor-2 (FGF2) Concentrate and Fibroblasts Cell Migration on Human Gingival Fibroblast (HGF) Culture - Dewi, Ni Ketut Ayu Feriyanti; Permatasari, Nur; Sujuti, Hidayat (Research Journal of Life Science, 2021)
The purpose of this study is to determine the effect of histatin-1 protein increasing the concentration of fibroblast growth factor (FGF2) and fibroblast cell migration in human gingival fibroblast (HGF) culture. The HGF cell culture used was obtained from odontectomy patients and was the result of the 4th passage. Cell culture was divided into 4 groups: HGF control group (without treatment) and treatment groups with 5µM, 10µM, and 20µM concentration of histatin-1 respectively. The amount of fibroblast growth factor 2 (FGF2) was quantified by using ELISA method. In vitro fibroblast cells migration was measured using scratch/wound healing assay method. FGF2 concentration and HGF cell migration were measured at hour 0, 3, 11, 24, and 48. The results of the One Way Anova statistical test difference between FGF 2 (ΔFGF2) at hour 24 showed a value of P = 0.042 (P≤0.05) and HGF cell migration at hour 11 showed a P value = 0.003 (P≤0.05). The conclusion of this study is that Histatin-1 Protein is able to increase the concentration of Fibroblast Growth Factor 2 (FGF2) and the migration of Human Gingival Fibroblast cells.